Analysis of the Effect of Competency and Workload on Performance Mediated by Work Motivation in Pattimura University Academic Employees - Maulany, Handry; Lewaherilla, Novalien Carolina; Leuhery, Ferdy (Jurnal Ekonomi, 2024)
The aim of this research is to analyze the influence of competency and workload on performance which is mediated by job satisfaction among employees in the Academic Division of Pattimura University.. This research is quantitative research. The research instrument used was a questionnaire. The number of samples taken was 39 respondentsThe data analysis method used is SEM PLS 3.0 to test the formative and reflective models between indicators. Based on the results of the data tests that have been carried out, the results obtained are thatCompetency(X1) has a positive and significant influence on performance (Y), and workload (X2) has a positive influence on performance. Competence has a positive and significant effect on work motivation. Workload has a positive and significant effect on performance. Likewise, work motivation has a positive and significant influence on performance. Apart from that, Competence has a positive and significant effect on performance mediated by work motivation (Z) and workload has a positive and significant effect on performance mediated by work motivation (Z). Thus it is clear that work motivation is able to mediate the influence of competency and workload on performance.